PENGARUH PENGEMBANGAN KARIR, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. RODATEKNINDO PURAJAYA KOTA BENGKULU - Yansa, Ramah Ardi; Bahrun, Khairul (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
Employees are a very valuable asset in achieving the company's goals. As an employee in doing a job, it must be as effective and efficient as possible. The quality and quantity of employees must be in accordance with the needs of employees and the placement of the workforce must also be appropriate and in accordance with their desires and expertise. Thus, employee performance will be better and more effective in supporting the realization of the company's goals. This thesis is to analyze the Influence of Career Development, Work Environment and Compensation on Employee Performance at PT. Rodateknindo Purajaya, Bengkulu City for sampling in this study is a total sampling of 60 employees of PT. Rodateknindo Purajaya, Bengkulu City. Multiple linear regression analysis with hypothesis testing, with the results of the study, it can be concluded that all independent variables, namely variables (Career Development, Work Environment and Compensation) simultaneously or together have a significant effect on the dependent variable, namely Employee Performance (Y). This means that Ho is rejected by Ha accepted. It can be concluded that Career Development, Work Environment and Compensation together have a significant effect on Employee Performance at PT. Rodateknindo Purajaya, Bengkulu City.Keywords: Career Development, Work Environment, Compensation, Employee Performance